2009
DOI: 10.1161/strokeaha.108.532499
|View full text |Cite
|
Sign up to set email alerts
|

Treating Visual Speech Perception to Improve Speech Production in Nonfluent Aphasia

Abstract: Background and Purpose-Several recent studies have revealed modulation of the left frontal lobe speech areas not only during speech production but also for speech perception. Crucially, the frontal lobe areas highlighted in these studies are the same ones that are involved in nonfluent aphasia. Based on these findings, this study examined the utility of targeting visual speech perception to improve speech production in nonfluent aphasia. Methods-Ten patients with chronic nonfluent aphasia underwent computerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 20 publications
5
53
0
5
Order By: Relevance
“…Beginning 5 minutes before the start of tDCS, this treatment was modeled after tasks used in previous studies that have resulted in improved naming accuracy in participants with aphasia. 1,5 Separate word lists were used for each treatment phase. 1…”
Section: Methodsmentioning
confidence: 99%
“…Beginning 5 minutes before the start of tDCS, this treatment was modeled after tasks used in previous studies that have resulted in improved naming accuracy in participants with aphasia. 1,5 Separate word lists were used for each treatment phase. 1…”
Section: Methodsmentioning
confidence: 99%
“…In the phonological condition, ` each heard word was accompanied by a video of a mouth saying the same word simultaneously. Such audio-visual integration has been shown to not only improve picture naming performance in aphasic speakers on both trained and untrained items but also created an "errorless learning" environment which patients found particularly enjoyable (Fridriksson, et al, 2009). Fridriksson and colleagues (2009) demonstrated that treatment of speech production in non-fluent aphasic patients can make use of motor speech perception, even though this process is also somewhat impaired in aphasia (Schmid & Ziegler, 2006).…”
Section: Training Protocolmentioning
confidence: 99%
“…A number of studies have identified that both phonological therapies that engage the dorsal route and semantic therapies that engage the ventral route can produce appreciable improvements in aphasic individuals (e.g., Barthel, Meinzer, Djundja, & Rockstroh, 2008;Bruce & Howard, 1987;Coelho, McHugh, & Boyle, 2000;Fridriksson et al, 2009;Lorenz & Ziegler, 2009;Nettleton & Lesser, 1991;Raymer, Thompson, Jacobs, & Le Grand, 1993). There are however, mixed opinions as to which types of therapy are superior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent meta-analysis studied the effects of TMS on neuropathic pain, including post-stroke supra-spinal related pain, and concluded that TMS provides a significant reduction invarious neuropathic pain conditions [21][22][23][24][25]. There are three main proposed mechanisms for this: 1) induction of neuroplasticity can allow for the brain to simply reorganize itself in a way that reverses the plasticity induced with neuropathic pain, 2) direct stimulation of descending inhibitory pathways to decrease the response to painful stimuli, 3) direct stimulation of endogenous opioid secretions [19].…”
Section: Transcranial Magnetic Stimulation/transcranial Direct Currenmentioning
confidence: 99%